Determination of the potential of pickle wastewater as feedstock for biopolymer production - Guventurk, Ayse; Ozturk, Dilara; Ozyildiz, Goksin; Ayisigi, Ezgi; Guven, Didem; Zengin, Gulsum Emel; Tas, Didem Okutman; Olmez-Hanci, Tugba; Pala-Ozkok, Ilke; Yagci, Nevin; Insel, Guclu; Cokgor, Emine (IWA Publishing, 2020)
Abstract Food industry wastewater (FIWW) streams with high organic content are among the most suitable and inexpensive candidates for polyhydroxyalkanoate (PHA) biopolymer production. Due to its high organic acid content, pickle industry wastewater (PIWW), can be considered as one of the prospective alternatives to petroleum-based polymers for PHA production. In this context, this study aimed to investigate the production of PHA with enriched microbial culture using PIWW. Two laboratory scale sequencing batch reactors (SBRs) were operated under aerobic dynamic feeding conditions at a sludge retention time of 8 days, with a total cycle duration of 24 hours. SBRs were fed with peptone mixture and PIWW. In-cycle analysis and batch respirometric tests were performed to evaluate PHA storage together with biodegradation kinetics. In-cycle analysis showed that maximum PHA content was 1,820 mgCOD/L, corresponding to 44% in the biomass (ratio of chemical oxygen demand (COD) to volatile suspended solids) for PIWW. Experimental results were also confirmed with activated sludge model simulations. As for the PHA composition, hydroxybutyrate was the major fraction. Model simulations proposed a unique conversion–degradation–storage pathway for the organic acid mixture. This paper presents a novel insight for better understanding of PHA biopolymer production using high saline FIWW.
Keywords: Biopolymers; Bioreactors; Sewage; Polyhydroxyalkanoates; Prospective Studies; Wastewater; Waste Disposal, Fluid